Antioxidative protection of haemoglobin microparticles (HbMPs) by PolyDopamine. (12th November 2018) - Baidukova, Olga; Wang, Quan; Chaiwaree, Saranya; Freyer, Dorette; Prapan, Ausanai; Georgieva, Radostina; Zhao, Lian; Bäumler, Hans
Abstract: Clinically applicable haemoglobin-based oxygen carriers (HBOCs) should neither induce immunological nor toxic reactions. Additionally, Hb should be protected against oxidation. In the absence of protective enzymes (superoxide dismutase (SOD) and catalase (CAT)) Hb is oxidized to MetHb and thus losing its function of oxygen delivery. Alternatively, polydopamine (PD), a scavenger of free radicals, could be used for Hb protection against oxidation Therefore, we synthetized HbMPs modified with PD. The content of functional haemoglobin in these PD-HbMPs was twice higher than that in the control HbMPs due to the protective antioxidant effect of PD. In addition, the PD-HbMPs exhibited a high scavenging activity of free radicals including H2 O2 and excellent biocompatibility. In contrast to monomeric dopamine, which has been shown to produce toxic effects on neurons due to formation of H2 O2, hydroxyl radicals and superoxide during the process of auto-oxidation, PD-HbMPs are not neurotoxic. Consequently, the results presented here suggest a great potential of PD-HbMPs as HBOCs.